Characteristics and Hedonic Evaluation of “Microgum” Chewable Gummy containing Moringa oleifera and Cucurbita moschata as a Potential Micronutrient Supplement - Arika Nur Insani; Adelia Widianti; Najwa Aulia Putri; Salsabiela Dwiyudrisa Suyudi (Duta Pharma Journal, 2026)
Background: Malnutrition and micronutrient deficiencies remain major public health problems, the the low acception of conventional supplements is one of contributing factor. Natural ingredients such as Moringa oleifera leaves and pumpkin seeds (Cucurbita moschata) contain bioactive compounds that may support the development of functional supplement products. Objective: This study aimed to formulate and evaluate chewable gummies (microgummy) containing Moringa oleifera leaf extract and Cucurbita moschata seed extract through physical, hedonic, and stability evaluations. Methods This quantitative experimental study used three formulations containing different concentrations of Moringa oleifera leaf extract (5%, 10%, and 15%). Extraction was performed by maceration using distilled water as the solvent. Evaluations included phytochemical screening, pH, swelling ratio, syneresis, dispersion time, weight uniformity, accelerated stability, and hedonic testing involving 15 panelists. Data were analyzed using One-Way ANOVA followed by Duncan’s post hoc test. Results: showed that Moringa oleifera leaf extract contained flavonoids, tannins, and saponins, while pumpkin seed extract showed positive results for alkaloids. All formulations had a pH value of 5. Swelling ratio values for F1, F2, and F3 were 2.00%, 2.02%, and 2.90%, while syneresis values were 3.125%, 2.752%, and 12.12%, respectively. Dispersion times were 16.59, 13.37, and 2.55 minutes. Only F1 met the weight uniformity requirement and dispersion standard (15-30 minutes). Accelerated stability testing at 40°C caused visible melting and deformation in all formulations. Hedonic evaluation showed that only aroma differed significantly among formulations (p<0.05). Formula F3 obtained the highest hedonic scores for color (4.20±0.41), taste (4.20±0.51), and texture (4.13±0.51). Conclusion: each formulation demonstrated different physicochemical characteristics which can vary because of the moringa leaves and pumpkin seed composition. The hedonic test shows that F3 achieved higher hedonic preference scores.